MicroRNAs in Tumor Cell Metabolism: Roles and Therapeutic Opportunities - Pedroza-Torres, Abraham; Romero-Córdoba, Sandra L.; Justo-Garrido, Montserrat; Salido-Guadarrama, Iván; Rodríguez-Bautista, Rubén; Montaño, Sarita; Muñiz-Mendoza, Rodolfo; Arriaga-Canon, Cristian; Fragoso-Ontiveros, Verónica; Álvarez-Gómez, Rosa María; Hernández, Greco; Herrera, Luis A. (Frontiers in Oncology, 2019)
Dysregulated metabolism is a common feature of cancer cells and is considered a hallmark of cancer. Altered tumor-metabolism confers an adaptive advantage to cancer cells to fulfill the high energetic requirements for the maintenance of high proliferation rates, similarly, reprogramming metabolism confers the ability to grow at low oxygen concentrations and to use alternative carbon sources. These phenomena result from the dysregulated expression of diverse genes, including those encoding microRNAs (miRNAs) which are involved in several metabolic and tumorigenic pathways through its posttranscriptional-regulatory activity. Further, the identification of key actionable altered miRNA has allowed to propose novel targeted therapies to modulated tumor-metabolism. In this review, we discussed the different roles of miRNAs in cancer cell metabolism and novel miRNA-based strategies designed to target the metabolic machinery in human cancer.